2018
DOI: 10.3389/fphar.2018.00636
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 Activation by Post-ischemic Treatment With Lumbrokinase Protects Against Myocardial Ischemia-Reperfusion Injury

Abstract: Lumbrokinase is used as an oral supplement to support and maintain healthy cardiovascular function, and to treat cardiovascular diseases in clinical for more than 10 years. Up until now, the mechanism of the cardioprotective effects of post-ischemic treatment with lumbrokinase has remained unclear. We therefore investigated the signaling pathways involved in the amelioration of myocardial ischemia-reperfusion (I-R) injury in rats treated with lumbrokinase 20 min after myocardial ischemia. Compared to vehicle-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…FoxO1, an important forhead transcription factor in the cardiovascular system [ 109 ], participates in the process of substrate metabolism and cell proliferation [ 110 ]. SIRT1 also has the capacity to deacetylase FoxO1 and repress its transcriptional activity during I/R, which acts as a pivotal part in controlling the increase of manganese superoxide dismutase (MnSOD) and inhibiting oxidative stress in cardiac myocytes [ 111 , 112 ] ( Figure 1 ). Consistently, the upregulation of FoxO1 was significantly enhanced with the increased expression of antioxidant MnSOD in cardiac-specific SIRT1 transgenic mice under ischemic stress [ 111 , 112 ].…”
Section: Role Of Sirt1 In the Redox Homeostasis During Myocardialmentioning
confidence: 99%
“…FoxO1, an important forhead transcription factor in the cardiovascular system [ 109 ], participates in the process of substrate metabolism and cell proliferation [ 110 ]. SIRT1 also has the capacity to deacetylase FoxO1 and repress its transcriptional activity during I/R, which acts as a pivotal part in controlling the increase of manganese superoxide dismutase (MnSOD) and inhibiting oxidative stress in cardiac myocytes [ 111 , 112 ] ( Figure 1 ). Consistently, the upregulation of FoxO1 was significantly enhanced with the increased expression of antioxidant MnSOD in cardiac-specific SIRT1 transgenic mice under ischemic stress [ 111 , 112 ].…”
Section: Role Of Sirt1 In the Redox Homeostasis During Myocardialmentioning
confidence: 99%
“…Yu et al 31 have indicated that melatonin ameliorates IR-induced oxidative stress and endoplasmic reticulum stress via activating SIRT1 signaling in type 2 diabetic rats. Wang et al 32 have proved that post-ischemic treatment with lumbrokinase attenuates myocardial IR injury through the activation of Sirt1 signaling. Lin et al 33 have demonstrated that the activation of SIRT1/Nrf2 signaling induced by Rutin contributes to the reduced oxidative stress and apoptosis of cardiomyocytes in rats with myocardial IR injury.…”
Section: Sirt1mentioning
confidence: 99%
“…The activity of SIRT1 deacetylase is significantly increased during stress. Deacetylation of SIRT1 downregulated transcriptional function of p53 to induce cell survival [16,17]. An increase in SIRT1 deacetylase activity can inhibit stress-induced cell apoptosis and oxidative stress injury via activation of SIRT1-FOXO1/p53 signaling [18].…”
Section: Introductionmentioning
confidence: 99%